Pengembangan Bahan Ajar Media Pembelajaran Matematika Dan Teknologi Informasi Komunikasi - Buyung Buyung; Zulyadaini Zulyadaini (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
There are no teaching materials used in learning media and information communication technology specifically for mathematics. The existing material is still general in nature so it is difficult for students to apply it to making mathematics-related media. Therefore, it is necessary to develop teaching materials for mathematics learning media and information communication technology that are specifically related to mathematics. In the implementation of research using research and development methods using the instructional development model (MPI). The subjects were FKIP even semester students. In collecting data using observation, interviews and questionnaires. Data analysis used descriptive qualitative. The results of the study obtained feasibility in terms of design validation with 89% feasibility, expert validation with 90% feasibility and material expert validation obtained 90.76% feasibility. In addition, the results of the one to one learner obtained a feasibility result of 93.3%. Followed by a small group trial obtaining a feasibility of 92.%. Then in the field trial, it obtained a feasibility of 91.6%. Based on these results, it is concluded that teaching materials are suitable for use in learning.